Treatment related toxicities with combination BRAF and MEK inhibitor therapy in resected stage III melanoma - Homan, Morgan; Warrier, Govind; Lao, Christopher D.; Yentz, Sarah; Kraft, Shawna; Fecher, Leslie A. (Frontiers in Oncology, 2022)
Abstract Combination dabrafenib (D) and trametinib (T) is an FDA approved adjuvant therapy for patients with resected stage III BRAF-mutant melanoma. We describe treatment-related toxicities with adjuvant D+T in a real-world population through a retrospective case series. The primary endpoint was development of toxicities. Results: Eighteen of the 20 patients (90%) required at least one treatment interruption due to adverse events (AEs), 11 patients (55%) required a dose reduction and 14 (70%) permanently discontinued therapy due to an AE. The 9 patients who did not require dose reduction had been initiated on a lower starting dose of dabrafenib. The most common treatment-limiting AEs were recurrent pyrexia and chills (85%) and liver laboratory abnormalities (50%). The median total time on therapy was 148.5 days (range 19-383), 40.7% (range 5.2-100%) of the intended one-year duration. Conclusion: Adjuvant treatment of melanoma with combination D+T is associated with treatment-limiting toxicities in the majority of this patient group. Patients should be carefully monitored throughout therapy.